Developing students’ aptitudes through University-Industry collaboration (2015)
In addition to the engineering knowledge base that has been traditionally taught, today’s undergraduate engineering students need to be given the opportunity to practice a set of skills that will be demanded to them by future employers, namely: creativity, teamwork, problem solving, leadership and the ability to generate innovative ideas. In order to achieve this and educate engineers with both in-depth technical knowledge and professional skills, universities must carry out their own innovating and find suitable approaches that serve their students. This article presents a novel approach that involves university-industry collaboration. It is based on creating a student community for a particular company, allowing students to deal with real industry projects and apply what they are learning in the classroom. A sample project for the German sports brand adidas is presented, along with the project results and evaluation by students and teachers. The university-industry collaborative approach is shown to be beneficial for both students and industry.